U-shaped relationship between birth weight and childhood blood pressure in China - Lai, Chong (BMC Pediatr, 2019)
BACKGROUND: The relationship between birth weight and blood pressure has not been well explored in Chinese children and adolescents. The aim of this study was to investigate the relationship between birth weight and childhood blood pressure in China. METHODS: A total of 15324 children and adolescents (7919 boys and 7405 girls) aged 7–17 years were stratified into six birth weight groups. Analysis of covariance and binary logistic regression were used to analyse the relationship between birth weight and blood pressure while controlling for potential confounding factors, including age, gestational age, season of birth and area of residence. RESULTS: The group with birth weights from 2500 to 2999 g had the lowest prevalence of hypertension (8.9%). Lower birth weight children (< 2000 g) had significantly higher systolic blood pressure (SBP) (106.00 ± 0.72, P = 0.017), and children with heavier birth weights also had higher SBP (3500–3999 g, 105.13 ± 0.17, P < .001; ≥ 4000 g, 105.96 ± 0.27, P < .001). No significant relationship was found between birth weight and diastolic blood pressure (DBP). The overall rate of hypertension was 10.8% (12.1% in boys and 9.4% in girls). The median weight group (2500–2999 g) had the lowest rate of hypertension (8.9%). Compared with children in the median weight group, children with lower birth weight had a higher prevalence of hypertension (< 2000 g, OR = 1.85, 95% CI = 1.25–2.74; 2000–2499 g, OR = 1.57, 95% CI = 1.15–2.13), and groups with higher birth weights also had higher risks of hypertension (3500–3999 g, OR = 1.22, 95% CI = 1.02–1.45; ≥ 4000 g, OR = 1.42, 95% CI = 1.16–1.74). CONCLUSIONS: Excluding the confounding effect of obesity, a U-shaped relationship between birth weight and risk of hypertension was found in children and adolescents in Chinese cities. Birth weight significantly influences SBP but has a minimal effect on DBP. Further basic research on foetal development and programming may shed light on this phenomenon.